2022
DOI: 10.1590/s1677-5538.ibju.2021.0405
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: The impact on urolithiasis treatment in Brazil

Abstract: Introduction: It has been more than a year since the fi rst case of Covid-19 was diagnosed in Brazil, and its most problematic feature is the oversaturation of the healthcare system capacity. Urolithiasis is a disease that requires timely and appropriate management. The present study aimed to evaluate the impact of the pandemic in hospital admissions for urolithiasis in the Brazilian public healthcare system. Materials and Methods: In this cross-sectional study, hospital admissions were obtained from the Brazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…Other studies have reported a decrease in urological presentations during the COVID‐19 pandemic [22–25]. We therefore predicted that during the pandemic patients with ureteric colic would have delayed presenting to hospital and therefore have been a more unwell cohort.…”
Section: Discussionmentioning
confidence: 95%
“…Other studies have reported a decrease in urological presentations during the COVID‐19 pandemic [22–25]. We therefore predicted that during the pandemic patients with ureteric colic would have delayed presenting to hospital and therefore have been a more unwell cohort.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have demonstrated a decrease in non-COVID-related hospital admissions, including reductions in elective procedures (1)(2)(3)(4)(5). In Germany, non-COVID overall inpatient admissions decreased by 35% after the lockdown announcement, with even admissions for critical care conditions such as cancer treatment significantly reduced (4).…”
Section: Commentmentioning
confidence: 99%
“…It demands populational screening with multiple clinic visits, prostate biopsies, imaging for staging, and finally, the treatment that comprehends surgery, radiotherapy, androgen deprivation therapy (ADT), and chemotherapy (9). Some studies have demonstrated the impact of the COVID-19 pandemic on hospital admissions in chronic conditions and non-covid related emergencies (2)(3)(4)(5). In Brazil, many health care institutions had their non-urgent procedures and elective surgeries suspended for months to concentrate economic and human resources to respond to the COVID-19 outbreak waves (10).…”
Section: Commentmentioning
confidence: 99%
“…Other studies have reported a decrease in urological presentations during the COVID-19 pandemic 2124 We therefore predicted that during the pandemic patients with ureteric colic would have delayed presenting to hospital and therefore have been a more unwell cohort. However, in our data, rates of AKI and active infection were lower in the pandemic patient cohort suggesting that these patients did not delay their presentation long enough to impact their clinical condition.…”
Section: Discussionmentioning
confidence: 98%